STUDENTS’ PERSPECTIVES OF BOOK CREATOR-BASED E-MODULE FOR LEARNING TOEIC PRACTICE - Dien Novita; Santy Christinawati (IKIP Siliwangi, 2023)
Learning English is highly desired and essential for EFL learners. Students are expected to be able to demonstrate their language skills via a language proficiency test. TOEIC is a language proficiency test that most EFL students, particularly vocational students, must learn and master. However, students frequently encounter difficulties when administering the TOEIC test. Improving students' comprehension of the TOEIC test practice requires a good strategy. The English 1 class is considered to be the class that discusses TOEIC strategies, and the Book Creator-based e-module is one of the suitable media to encourage students' ability to comprehend. The study's goal is to learn about students' perspectives on using the Book Creator-based e-module and the implementation of the Book Creator as an e-module for learning TOEIC practice. This study used a descriptive quantitative approach with one group of 28 students from the first semester of Polytechnic LP3I Bandung. The findings showed that students responded positively to the Book Creator as an e-module, and the Book Creator can encourage the learning process and improve students' enthusiasm to practice the TOEIC test. Keywords: Students’ Perspectives; Book Creator; E-Module; TOEIC Practice